Anti-aging polyurethane coating and production process thereof

By adopting aging-resistant polyurethane coating with a specific formula, the problem of short service life, not wear resistance and easy to fall off of the waterproof coating is solved, and the high elongation and aging resistance of the coating in long-term use is achieved.

CN119775877AInactive Publication Date: 2025-04-08DONGGUAN MAYBACH POLYMER MATERIALS CO LTD

Patent Information

Application Number
CN202411982770.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing waterproof coating has a short service life, is not wear-resistant and is easy to fall off on the surface of the straw magnesium cement hollow strip substrate.

Method used

A resistant polyurethane coating is used, which includes component A and component B. Component A is composed of polyether polyols, polyester polyols, silicone modified chain extenders, etc. Component B includes rock flakes, flash crystals or colored sand. It is prepared through specific formulas and processes to form a polyurethane coating with high elongation.

Benefits of technology

The coating can maintain good elastic properties after long-term use, significantly improves its service life, and has excellent water, heat and aging resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-aging polyurethane coating and a production process thereof, and relates to the technical field of floor coating materials. The anti-aging polyurethane coating comprises a component A and a component B, the component A is an elastomer, the component B is at least one of rock slices, flash crystals or colored sand, and the mass ratio of the component A to the component B is (4-6): 1; the component A is at least prepared from the following raw materials in parts by mass: 80 to 100 parts of polyether polyol, 80 to 100 parts of polyester polyol, 30 to 40 parts of amino polyether, 20 to 40 parts of an organic silicon modified chain extender, 30 to 35 parts of diphenylmethane diisocyanate, 105 to 160 parts of long-chain paraffin, 20 to 30 parts of an environment-friendly plasticizer, 1 to 4 parts of a dispersing agent, 10 to 15 parts of a molecular sieve, 1 to 3 parts of an antioxidant and 30 to 40 parts of kaolin; 400-450 parts of modified calcium carbonate powder, 8-12 parts of trihydroxypropane and 1-2 parts of a defoaming agent. The anti-aging polyurethane coating prepared by the invention has high extensibility, water resistance, heat resistance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of floor coating materials, and in particular to an anti-aging polyurethane coating and a production process thereof. Background Art

[0002] With the continuous improvement of the national economic level, people pay more and more attention to sports and health. Floor materials have a broad space for development. Common floor materials are mostly PVC rolls. PVC rolls are a kind of thermoplastic rolls made of polyvinyl chloride resin as the main raw material through mixing, extrusion molding and vulcanization. The main problems are as follows: (1) PVC waterproof rolls are sensitive to temperature. They are easy to deform and soften at high temperatures, and easy to become brittle and crack at low temperatures. (2) Long-term exposure to sunlight will cause aging of PVC waterproof rolls, resulting in performance degradation. (3) When PVC waterproof rolls are damaged, they need to be replaced as a whole for maintenance, which is costly. (4) The rolls are bonded with glue, which is easy to fall off over time and cannot be seamlessly connected. It is easy to breed bacteria in a sterile environment. (5) The adhesion between the rolls and the base layer is not strong, and it is easy to have hollowing, cracking and other phenomena. (6) The loss is large. For irregular parts, the construction requirements are high and the cutting loss is large.

[0003] As one of the six major polymer synthetic materials, polyurethane (PU) has the characteristics of high strength, high hardness, high modulus and high elongation, as well as good oil resistance, low temperature resistance and wear resistance. It can be used as adhesives, coatings, fibers, plastics, rubbers, etc., and has a wide range of applications. Polyurethane flooring refers to the use of polyurethane floor coatings combined with a new type of solvent-free or water-based, pollution-free ground functional construction technology, which has anti-slip, anti-corrosion and wear-resistant flooring. Colored sand decorative flooring is a new type of composite decorative flooring composed of colored quartz sand and resin. Through the free combination of one or more different colors of colored quartz sand, colorful decorative colors and patterns are formed. Polyurethane colored sand floor combines the advantages of polyurethane floor and colored sand floor. It has good decorative effect, good mechanical, weather resistance, high and low temperature resistance, and corrosion resistance. Its comprehensive performance is excellent and it belongs to high-end floor material. It is suitable for places that need to resist heavy cutting and anti-slip, such as garages, warehouses, molds and machinery manufacturing workshops, etc. It can also be used in many industrial and commercial occasions, such as food and beverage industry, precision industry, pharmaceutical chemical industry, electronic manufacturing, clean rooms, laboratories and research institutions, water treatment and garbage disposal sites, metal processing and refineries, fiber production and textile mills, paper and pulp mills and other areas that require long-lasting wear resistance.

[0004] Although polyurethane materials have excellent properties and are widely used, they are consistent with other polymer materials. During transportation, storage and outdoor use, polyurethane will undergo light-induced degradation, photo-oxidative degradation, thermal-oxidative degradation, hydrolysis and microbial degradation. These degradation methods will cause the polyurethane structure to be destroyed and the groups to fall off. From the appearance morphology, it is manifested as brittleness or even cracking, yellowing and mechanical properties. We call these phenomena the aging degradation of polyurethane materials. The aging process of polyurethane materials is an irreversible process. Once aging degradation occurs, polyurethane products will lose their use value, which often has a fatal impact on their performance. Due to the various changes in the structure of polyurethane materials, the complex degradation process, and the many factors affecting the aging resistance, the material is not only determined by its own formula and processing technology, but also by external conditions such as temperature, humidity, light, oxygen (oxygen, ozone and atomic oxygen). The aging degradation mechanism of polyurethane materials under different environments is different. At present, my country's research on this issue is still in the initial research stage, with a large gap with foreign countries, and there are relatively few reports on related aspects. Therefore, how to effectively improve the aging resistance of polyurethane and increase the service life of polyurethane has become one of the problems to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-aging polyurethane coating and a production process thereof to solve the following technical problems:

[0006] The existing waterproof coating is coated on the surface of the straw magnesium cement hollow strip board substrate, but has the problems of short service life, poor wear resistance and easy falling off.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] An aging-resistant polyurethane coating and a production process thereof, comprising component A and component B, wherein the component A is an elastomer, the component B is at least one of rock flakes, scintillating crystals or colored sand, and 1. The mass ratio of the component A to the component B is 4-6:1;

[0009] Wherein, the A component is composed of at least the following raw materials in parts by mass:

[0010] 80-100 parts of polyether polyol, 80-100 parts of polyester polyol, 30-40 parts of amino polyether, 20-40 parts of silicone modified chain extender, 30-35 parts of diphenylmethane diisocyanate, 105-160 parts of long-chain paraffin, 20-30 parts of environmentally friendly plasticizer, 1-4 parts of dispersant, 10-15 parts of molecular sieve, 1-3 parts of antioxidant, 30-40 parts of kaolin, 400-450 parts of modified calcium carbonate powder, 8-12 parts of trihydroxypropane and 1-2 parts of defoaming agent.

[0011] As a further embodiment of the present invention: the preparation method of the organosilicon modified chain extender comprises at least the following steps:

[0012] Octylamine and γ-glycidyloxypropyltrimethoxysilane are mixed and stirred at room temperature for 30-40 minutes, and then stirred at 20° C. for 24-36 hours to obtain an organosilicon-modified chain extender.

[0013] As a further embodiment of the present invention, the molar ratio of the octylamine to the γ-glycidyloxypropyltrimethoxysilane is 1:1-1.1.

[0014] As a further solution of the present invention: the preparation method of the modified calcium carbonate powder comprises the following steps:

[0015] Dissolving ammonium cerium nitrate in nitric acid, adding fatty alcohol polyoxyethylene ether to obtain a cerium salt solution;

[0016] At 30° C., gradually adding anhydrous ethanol-ammonia aqueous solution to the cerium salt solution under constant stirring to obtain a nano-cerium dioxide sol;

[0017] The heavy calcium carbonate is dispersed in the nano-cerium dioxide sol under the action of ultrasound, immersed for 20-30 minutes, taken out, washed, dried, calcined at 500° C. for 2-4 hours, and then ground to obtain modified calcium carbonate powder.

[0018] As a further solution of the present invention: the mass ratio of the nano cerium dioxide to the heavy calcium carbonate is (1-3): (2-5).

[0019] As a further embodiment of the present invention: the concentration of the ammonium cerium nitrate in the cerium salt solution is 0.8-1 mol·L -1 The concentration of the fatty alcohol polyoxyethylene ether in the cerium salt solution is 4-6 g·L -1 The volume ratio of the anhydrous ethanol to the aqueous ammonia is 1:1, and the concentration of the aqueous ammonia is 1 mol·L -1 .

[0020] A method for preparing the aging-resistant polyurethane coating as described in any one of the above, comprising at least the following preparation steps:

[0021] Add the polyether polyol, polyester polyol, organosilicon modified chain extender, amino polyether, long-chain paraffin, environmentally friendly plasticizer, dispersant, molecular sieve, antioxidant, kaolin, modified calcium carbonate powder and trihydroxypropane in component A into a reaction kettle in proportion, disperse at high speed, and then vacuum dehydrate at 130-140° C. for 1-4 hours, then add diphenylmethyl diisocyanate to react for 4-5 hours, then add a defoamer, cool, and obtain an elastomer;

[0022] The elastomer is mixed evenly with component B to obtain an aging-resistant polyurethane coating.

[0023] As a further solution of the present invention: the polyether polyol is polyether polyol 2000, the polyester polyol is polyester polyol 1000, and the amino polyether is amino-terminated polyether T-5000.

[0024] As a further scheme of the present invention: the environmentally friendly plasticizer is at least one of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, dipropylene glycol dibenzoate or acetyl citrate tri-n-butyl ester, the dispersant is one or more of butyl stearate, pentaerythritol stearate, monostearate glyceryl, ethylene bisoleamide, ethylene bisstearamide, oleamide, erucamide, stearamide, zinc stearate or calcium stearate, the molecular sieve is at least one of 3A molecular sieve, 5A molecular sieve or 13X molecular sieve, the antioxidant is at least one of antioxidant 1076 and antioxidant 1010, and the defoaming agent is one of polyether siloxane copolymer emulsion or polydimethylsiloxane emulsion.

[0025] Beneficial effects of the present invention:

[0026] The present invention utilizes octylamine ring-opening γ-glycidyl ether oxygen propyl trimethoxy silane as a chain extender, and then utilizes polyether polyol, polyester polyol, amino polyether, diphenylmethane diisocyanate, trihydroxy propane, cerium dioxide modified heavy calcium carbonate, and other pigments and additives to synthesize polyurethane, polyester polyol as a soft segment to provide elasticity for the material, diphenylmethane diisocyanate and trihydroxy propane as a hard segment to provide rigidity and strength for the material, the combination of the soft segment and the hard segment gives the polyurethane excellent mechanical properties, the introduction of the silane-modified chain extender gives the polyurethane material water resistance and heat resistance, and the addition of cerium dioxide modified heavy calcium carbonate realizes that the polyurethane elastic coating effectively shields and blocks the aging and erosion of the coating film by ultraviolet rays in outdoor sunlight during long-term use. The high elongation and aging-resistant polyurethane coating involved in the present invention not only has excellent elongation at break, but also can continue to maintain good elastic properties after experiencing long-term aging conditions, thereby greatly improving the service life of the elastic coating, and can be widely used in various daily life scenes such as agriculture, industry, construction, and transportation.

[0027] The present invention utilizes octylamine ring-opening γ-glycidyl ether oxygen propyl trimethoxysilane to insert a long-chain alkyl group into siloxane and use it as a chain extender. Hydroxyl (-OH) and amino (-NH2) are utilized to form (-NHCOO-) and (-NHCONH-) with isocyanate (-NCO), and finally a polyurethane with high elongation is synthesized by stepwise addition. The organic silicon segment is introduced at the end and node of the polyurethane chain, and a Si-OH structure can be formed by hydrolysis, which not only provides an action site for reacting with a substrate and nanoparticles, but also the Si-OH structure can eventually form a stable Si iOS i bond. Many Si iOS i bonds are linked together to form a dense network structure, thereby enhancing the overall mechanical ability of the coating, and with the increase of the silane content, the degradation temperature is increased, the thermal stability is enhanced, and the heat resistance is improved. Ordinary polyurethane is a multi-hydrophilic group, and the polyurethane modified by siloxane will achieve better hydrophobicity and water resistance, and the siloxane will automatically gather on the surface of the coating, reduce the surface energy of the coating, and enhance the hydrophobicity and water resistance of the coating.

[0028] The invention utilizes cerium nitrate and fatty alcohol polyoxyethylene ether to prepare nanometer cerium dioxide sol, and modifies heavy calcium carbonate. Nanometer cerium dioxide is one of the materials for blocking ultraviolet rays. Nanometer cerium dioxide is adsorbed on the surface of heavy calcium carbonate particles. Heavy calcium carbonate plays the role of a network skeleton, and provides a good filling and accommodating space for nanometer cerium dioxide. When the modified heavy calcium carbonate is mixed with polyurethane, the fatty alcohol polyoxyethylene ether is attached to the surface of the particles to form a protective film, which weakens or shields various association forces between particles and prevents the agglomeration of particles. Under the action of the fatty alcohol polyoxyethylene ether, the modified calcium carbonate powder and the polyurethane can be fully fused, which can not only improve the hardness of the polyurethane, but also effectively avoid the problem of agglomeration of heavy calcium carbonate particles, thereby effectively avoiding the problem of agglomeration of nanometer cerium dioxide. The modified heavy calcium carbonate effectively captures free radicals excited by ultraviolet light in the coating and cuts off the oxidative degradation chain reaction, significantly inhibiting the aging degradation rate of the coating. It works synergistically with long-chain paraffin, environmentally friendly plasticizers, dispersants, molecular sieves, antioxidants and kaolin as pigments, fillers and additives, ultimately enabling the coating of the present invention to effectively maintain a high elongation after a long period of artificial aging experiments. DETAILED DESCRIPTION

[0029] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1 The preparation method of the organosilicon modified chain extender comprises the following steps:

[0031] Octylamine and γ-glycidyloxypropyltrimethoxysilane in a molar ratio of 1:1 were mixed and stirred in a single-necked flask at room temperature for 30 minutes, and then stirred at 20° C. for 24 hours to obtain an organosilicon-modified chain extender.

[0032] Embodiment 2 The preparation method of modified calcium carbonate powder comprises the following steps:

[0033] Under magnetic stirring, ammonium cerium nitrate was dissolved in nitric acid to prepare a 0.5 mol·L -1 The aqueous solution of cerium salt is added with fatty alcohol polyoxyethylene ether to obtain a cerium salt solution, wherein the concentration of fatty alcohol polyoxyethylene ether in the cerium salt solution is 10g·L -1 The concentration of ammonium cerium nitrate is 0.3 mol·L -1 ;

[0034] Anhydrous ethanol and 1 mol·L -1 ammonia water, and anhydrous ethanol-ammonia solution is prepared at a volume ratio of 1:1, and the cerium salt solution prepared above is placed on a magnetic stirrer at a temperature of 30°C, and the anhydrous ethanol-ammonia solution is gradually added dropwise under continuous stirring until a nano-cerium dioxide sol is obtained;

[0035] Heavy calcium carbonate with a mass ratio of 3:1 to nano-cerium dioxide is dispersed in the above-mentioned nano-cerium dioxide sol under ultrasonic action, immersed for 20 minutes, taken out, washed, dried, calcined at 500°C for 2 hours, and then ground to obtain modified calcium carbonate powder.

[0036] Embodiment 3 The preparation method of modified calcium carbonate powder comprises the following steps:

[0037] Under magnetic stirring, ammonium cerium nitrate was dissolved in nitric acid to prepare a 0.5 mol·L -1 The aqueous solution of cerium salt is added with fatty alcohol polyoxyethylene ether to obtain a cerium salt solution, wherein the concentration of fatty alcohol polyoxyethylene ether in the cerium salt solution is 10g·L -1 The concentration of ammonium cerium nitrate is 0.3 mol·L -1 ;

[0038] Anhydrous ethanol and 1 mol·L -1 ammonia water, and anhydrous ethanol-ammonia solution is prepared at a volume ratio of 1:1, and the cerium salt solution prepared above is placed on a magnetic stirrer at a temperature of 30°C, and the anhydrous ethanol-ammonia solution is gradually added dropwise under continuous stirring until a nano-cerium dioxide sol is obtained;

[0039] Heavy calcium carbonate with a mass ratio of 2:1 to nano-cerium dioxide is dispersed in the above-mentioned nano-cerium dioxide sol under ultrasonic action, immersed for 20 minutes, taken out, washed, dried, calcined at 500°C for 2 hours, and then ground to obtain modified calcium carbonate powder.

[0040] Embodiment 4 The preparation method of the aging-resistant polyurethane coating comprises the following steps:

[0041] 100 parts by mass of polyether polyol 2000, 100 parts by mass of polyester polyol 1000, 40 parts by mass of the organosilicon modified chain extender prepared in Example 1, 40 parts by mass of amino-terminated polyether T-5000, 160 parts by mass of long-chain paraffin, 20 parts by mass of environmentally friendly plasticizer 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 2 parts by mass of dispersant butyl stearate, 15 parts by mass of 3A molecular sieve, 2 parts by mass of antioxidant 1010, 40 parts by mass of kaolin, 430 parts by mass of modified calcium carbonate powder prepared in Example 2 and 10 parts by mass of trihydroxypropane in component A are added to a reactor in proportion, dispersed at high speed, and then vacuum dehydrated at 130° C. for 2 h, then 32 parts by mass of diphenylmethyl diisocyanate are added to react for 4 h, and then 2 parts by mass of defoaming agent polyether siloxane copolymer emulsion are added, cooled, and an elastomer is obtained;

[0042] The prepared elastomer was evenly mixed with 200 parts by mass of colored sand to obtain an aging-resistant polyurethane coating.

[0043] The preparation method of embodiment 5 anti-aging polyurethane coating comprises the following steps:

[0044] 100 parts by mass of polyether polyol 2000, 100 parts by mass of polyester polyol 1000, 40 parts by mass of the organosilicon modified chain extender prepared in Example 1, 40 parts by mass of amino-terminated polyether T-5000, 160 parts by mass of long-chain paraffin, 20 parts by mass of environmentally friendly plasticizer 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 2 parts by mass of dispersant butyl stearate, 15 parts by mass of 3A molecular sieve, 2 parts by mass of antioxidant 1010, 40 parts by mass of kaolin, 430 parts by mass of modified calcium carbonate powder prepared in Example 3 and 10 parts by mass of trihydroxypropane in component A are added to a reactor in proportion, dispersed at high speed, and then vacuum dehydrated at 130° C. for 2 h, then 32 parts by mass of diphenylmethyl diisocyanate are added to react for 4 h, and then 2 parts by mass of defoaming agent polyether siloxane copolymer emulsion are added, cooled, and an elastomer is obtained;

[0045] The prepared elastomer was evenly mixed with 200 parts by mass of colored sand to obtain an aging-resistant polyurethane coating.

[0046] Comparative Example 1 omits the step of preparing modified calcium carbonate powder. Compared with Example 5, Comparative Example 1 only replaces the mass of modified calcium carbonate powder prepared in Example 3 added in Example 5 with unmodified heavy calcium carbonate powder, and the remaining components and preparation method are exactly the same as those in Example 5.

[0047] Comparative Example 2 omits the step of preparing the organosilicon-modified chain extender. Compared with Example 5, Comparative Example 2 only replaces the mass of the organosilicon-modified chain extender prepared in Example 3 added in Example 5 with unmodified octylamine, and the remaining components and preparation method are exactly the same as those in Example 5.

[0048] Comparative Example 3 omits the steps of preparing the organosilicon-modified chain extender and the modified calcium carbonate powder. Compared with Example 5, Comparative Example 2 only replaces the mass of the organosilicon-modified chain extender prepared in Example 3 added in Example 5 with unmodified octylamine, and replaces the mass of the modified calcium carbonate powder prepared in Example 3 added with unmodified heavy calcium carbonate powder. The remaining components and preparation method are exactly the same as those in Example 5.

[0049] Performance Testing

[0050] Tensile strength and elongation at break: tested according to GB / T528-1998 "Determination of tensile properties of vulcanized rubber and thermoplastic rubber"; the test results are shown in the table below;

[0051] Heat resistance evaluation: After curing the film for 7 days at (23±5)℃ and (55±5)%RH, cut it into dumbbell-shaped test pieces and heat-age it at 120℃ for 200h. Then test the elongation retention at break. The test results are shown in the table below.

[0052] Evaluation of heat resistance performance: After the dumbbell-shaped test piece (preparation method is the same as heat resistance performance evaluation) is water aged in a water tank at 40°C for 200 hours, the elongation retention rate at break is tested; the test results are shown in the table below;

[0053] UV aging resistance evaluation: Dumbbell-shaped test pieces (prepared in the same way as heat resistance evaluation) were placed under ultraviolet light with an intensity of (400±10)μW / cm 2 , under the real environment of relative humidity of 2%, after aging with ultraviolet light for 200h, the elongation retention rate at break was tested; the test results are shown in the table below;

[0054] Tensile strength / um Elongation at break / % Water resistance / % Heat resistance / % Aging resistance / % Example 4 2.0 520 96 96 95 Example 5 1.9 520 96 96 96 Comparative Example 1 1.7 470 85 84 55 Comparative Example 2 1.2 400 72 70 82 Comparative Example 3 1.0 380 65 64 46

[0055] As shown in Table 1, the aging-resistant polyurethane prepared in Examples 4-5 of the present invention has excellent water resistance, heat resistance and aging resistance, and can be used for floor materials. In Comparative Example 1, unmodified calcium carbonate powder was added, and the obtained polyurethane had poor aging resistance to ultraviolet rays. In Comparative Example 2, unmodified chain extender was added, and the mechanical properties, water resistance and heat resistance of the obtained polyurethane decreased. In Comparative Example 3, both the calcium carbonate powder and the chain extender added were unmodified, and the performance of the obtained polyurethane in all aspects was poor, indicating that the polyurethane prepared in this application has better tensile strength and elongation at break, and has more excellent water resistance, heat resistance and aging resistance.

[0056] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. An aging-resistant polyurethane coating, characterized in that: The invention comprises a component A and a component B, wherein the component A is an elastomer, the component B is at least one of rock flakes, scintillating crystals or colored sand, and the mass ratio of the component A to the component B is 4-6:1; Wherein, the A component is composed of at least the following raw materials in parts by mass: 80-100 parts of polyether polyol, 80-100 parts of polyester polyol, 30-40 parts of amino polyether, 20-40 parts of silicone modified chain extender, 30-35 parts of diphenylmethane diisocyanate, 105-160 parts of long-chain paraffin, 20-30 parts of environmentally friendly plasticizer, 1-4 parts of dispersant, 10-15 parts of molecular sieve, 1-3 parts of antioxidant, 30-40 parts of kaolin, 400-450 parts of modified calcium carbonate powder, 8-12 parts of trihydroxypropane and 1-2 parts of defoaming agent.

2. The aging-resistant polyurethane coating according to claim 1, characterized in that: The preparation method of the organosilicon modified chain extender comprises at least the following steps: Octylamine and γ-glycidyloxypropyltrimethoxysilane are mixed and stirred at room temperature for 30-40 minutes, and then stirred at 20° C. for 24-36 hours to obtain an organosilicon-modified chain extender.

3. The aging-resistant polyurethane coating according to claim 2, characterized in that: The molar ratio of the octylamine to the γ-glycidyloxypropyltrimethoxysilane is 1:1-1.

1.

4. The aging-resistant polyurethane coating according to claim 1, characterized in that: The preparation method of the modified calcium carbonate powder comprises the following steps: Dissolving ammonium cerium nitrate in nitric acid, adding fatty alcohol polyoxyethylene ether to obtain a cerium salt solution; At 30° C., gradually adding anhydrous ethanol-ammonia aqueous solution to the cerium salt solution under constant stirring to obtain a nano-cerium dioxide sol; The heavy calcium carbonate is dispersed in the nano-cerium dioxide sol under the action of ultrasound, immersed for 20-30 minutes, taken out, washed, dried, calcined at 500° C. for 2-4 hours, and then ground to obtain modified calcium carbonate powder.

5. The anti-aging polyurethane coating according to claim 4, characterized in that: The mass ratio of the nano cerium dioxide to the heavy calcium carbonate is (1-3): (2-5).

6. The anti-aging polyurethane coating according to claim 4, characterized in that: The concentration of the ammonium cerium nitrate in the cerium salt solution is 0.8-1 mol·L -1 The concentration of the fatty alcohol polyoxyethylene ether in the cerium salt solution is 4-6 g·L -1 The volume ratio of the anhydrous ethanol to the aqueous ammonia is 1:1, and the concentration of the aqueous ammonia is 1 mol·L -1 .

7. A method for preparing an aging-resistant polyurethane coating according to any one of claims 1 to 6, characterized in that: The method comprises at least the following preparation steps: Add the polyether polyol, polyester polyol, organosilicon modified chain extender, amino polyether, long-chain paraffin, environmentally friendly plasticizer, dispersant, molecular sieve, antioxidant, kaolin, modified calcium carbonate powder and trihydroxypropane in component A into a reaction kettle in proportion, disperse at high speed, and then vacuum dehydrate at 130-140° C. for 1-4 hours, then add diphenylmethyl diisocyanate to react for 4-5 hours, then add a defoamer, cool, and obtain an elastomer; The elastomer is mixed evenly with component B to obtain an aging-resistant polyurethane coating.

8. The method for preparing an aging-resistant polyurethane coating according to claim 7, characterized in that: The polyether polyol is polyether polyol 2000, the polyester polyol is polyester polyol 1000, and the amino polyether is amino-terminated polyether T-5000.

9. The method for preparing an aging-resistant polyurethane coating according to claim 7, characterized in that: The environmentally friendly plasticizer is at least one of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, dipropylene glycol dibenzoate or acetylcitrate tri-n-butyl ester, the dispersant is one or more of butyl stearate, pentaerythritol stearate, monostearate glyceryl, ethylene bisoleamide, ethylene bisstearamide, oleamide, erucamide, stearamide, zinc stearate or calcium stearate, the molecular sieve is at least one of 3A molecular sieve, 5A molecular sieve or 13X molecular sieve, the antioxidant is at least one of antioxidant 1076 and antioxidant 1010, and the defoaming agent is one of polyether siloxane copolymer emulsion or polydimethylsiloxane emulsion.

Citation Information

Patent Citations

  • Composite nano cerium dioxide sol preparation method

    CN101386419A

  • Single-component moisture-curable organic silicon modified polyurethane waterproof paint and preparation method

    CN105694702A

Cited By

  • Antibacterial stain-resistant thermoplastic polyurethane elastomer and preparation method thereof

    CN122404662A